Discourses of faith: popular religiosity in the work of Jorge Hidalgo and José Emilio Leyva - Yuricel Moreno Zaldívar (Khazanah Theologia, 2023)
The article deals with the representation of popular religiosity in the work of the artists Jorge Hidalgo Pimentel and José Emilio Leyva Azze. From engraving, painting, drawing and sculpture, both have recreated deities, various symbolic elements, orality, among other aspects that are part of the social imaginary in Cuba. The text chooses representative works of stages in which the artists assume the theme with greater permanence within their work. The examination has been carried out from a qualitative perspective that overlaps the formal analysis of the works and the hermeneutic method, as a generalizing interpretative framework. With different trajectories, motivations and poetics, Jorge Hidalgo and José Emilio Leyva contribute visions that demonstrate the survival of cultural practices rooted in the Cuban people, since they form an intrinsic part of their identity. The works contribute to the safeguarding of these manifestations of intangible cultural heritage. The evaluations given in the text also provide elements that enrich the critical body on this matter within the Holguín visual arts.